2016
DOI: 10.1073/pnas.1600354113
|View full text |Cite
|
Sign up to set email alerts
|

Dimer interface of bovine cytochrome c oxidase is influenced by local posttranslational modifications and lipid binding

Abstract: Bovine cytochrome c oxidase is an integral membrane protein complex comprising 13 protein subunits and associated lipids. Dimerization of the complex has been proposed; however, definitive evidence for the dimer is lacking. We used advanced mass spectrometry methods to investigate the oligomeric state of cytochrome c oxidase and the potential role of lipids and posttranslational modifications in its subunit interfaces. Mass spectrometry of the intact protein complex revealed that both the monomer and the dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 58 publications
2
27
0
1
Order By: Relevance
“…In seminal studies on mammalian C c O, Kadenbach and co-workers demonstrated the regulation of activity and efficiency by many physiological ligands, including ATP, ADP, and thyroxin [14]. They further recognized that the enzyme was subject to phosphorylation, an early observation that is now supported by a great deal of data indicating numerous phosphorylation [5] and acetylation sites in mammalian C c O [6,7]. Equally significant was the discovery by the Kadenbach group that many isoforms of the nuclear encoded subunits existed and were differentially expressed in different tissues [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In seminal studies on mammalian C c O, Kadenbach and co-workers demonstrated the regulation of activity and efficiency by many physiological ligands, including ATP, ADP, and thyroxin [14]. They further recognized that the enzyme was subject to phosphorylation, an early observation that is now supported by a great deal of data indicating numerous phosphorylation [5] and acetylation sites in mammalian C c O [6,7]. Equally significant was the discovery by the Kadenbach group that many isoforms of the nuclear encoded subunits existed and were differentially expressed in different tissues [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these limitations, the approaches discussed have achieved significant success in identifying a range of lipid interaction sites on membrane proteins, controlled and tested against experimental data including mass spectrometry (Gupta et al, 2017;Liko et al, 2016;Yen et al, 2018), crystallographic (Arnarez et al, 2013a;Schmidt et al, 2013;Van Eerden et al, 2017;Zeppelin et al, 2018), NMR spectroscopy Hedger et al, 2016b), and mutational functional data (Hedger et al, 2016a;Hedger et al, 2015;Stansfeld et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, only Cox5 (homologous to mammalian subunit IV) has isoforms but in mammalian CcOs isoforms of subunits IV, VIa, VIb, VIc, VIIa, VIIb and VIII have been found. Several subunits house sites that may become phosphorylated [Hüttemann et al, 2012], acetylated [Liko et al, 2016] or can bind nucleotides [Kadenbach and Hüttemann, 2015;Arnold, 2012]. Specific functions of some of these isoforms, their post-translational modifications and ligand binding sites have been suggested, though the supporting data in many cases remain inconsistent.…”
Section: Supernumerary and Additional Subunitsmentioning
confidence: 99%